Weeds in raw sugar cane renovation area with different systems of management on soil and green manure succession = Plantas daninhas em área de reforma de cana crua com diferentes manejos do solo e adubos verdes em sucessão - Willians Cesar Carrega; Everton Luis Finoto; José de Anchieta Alves de Albuquerque; Maria Beatriz Bernardes Soares; Denizart Bolonhezi (Agro@mbiente On-line, 2012)
The renewal of plantations is important to maintain high agricultural productivity of the culture of sugar cane and is performed after 5 cuts. In order to compare the residual effects of crop succession in different planting systems on the spontaneous occurrence of weeds in the area of reform of sugarcane, the experiment was done on Acrisol eutrophic soil, located in the city of Novais, São Paulo, in sugar cane harvested without prior burning in the last five cuts. The randomized block design with treatments arranged in split plot and arranged in four replications was used. The main treatments consisted of three cropping systems, conventional tillage, minimum tillage, and no tillage. Secondary treatments consisted of two choices of green manure (sunnhemp and velvet bean) and a fallow plot. After 180 days of harvest of sugar cane was counted the number of weeds.m-2 and determined the dry mass of shoots, calculating their phytosociological index. Among the management systems of soil, the no tillage system showed a suppressive effect of weeds, resulting in fewer plants, less dry mass of plants and less variety of species, suppressing species that are considered important in the culture of sugar cane. The minimum tillage method revealed intermediate results and conventional tillage was most affected by weeds. Among the green manure planted in succession to sugar cane, the velvet bean is highlighted, and shows suppressive effect of the most important weeds in fields planted with conventional soil tillage. = A renovação dos canaviais é importante para manter elevada a produtividade agrícola da cultura e é realizada em média após cinco cortes, com o objetivo de comparar o efeito residual das culturas de sucessão nos diferentes sistemas plantio sobre a ocorrência espontânea de plantas daninhas em área de reforma de cana crua, instalou-se o experimento sobre ARGISSOLO VERMELHO-AMARELO Eutroférrico, localizado no município de Novais-SP, em canavial colhido sem queima prévia nos últimos cinco cortes. Utilizou-se delineamento experimental blocos casualizados, com os tratamentos arranjados em parcelas sub-divididas, com quatro repetições. Os tratamentos principais consistiram dos três sistemas de cultivo; convencional, cultivo mínimo e plantio direto. Os tratamentos secundários foram constituídos de duas opções de adubos verdes (crotalária e mucuna) e uma parcela em pousio. Após 180 dias da colheita da cana-de-açúcar contou-se o número de plantas daninhas m-2e determinou-se a massa seca da parte aérea, calculando seus índices fitossociológicos. Dentre os sistemas de manejo do solo o plantio direto mostrou um efeito supressor das plantas daninhas, resultando em menor número de plantas, menor massa seca de plantas e menor variedade de espécies, suprimindo espécies consideradas importantes na cultura da cana-de-açúcar, sendo o cultivo mínimo o tratamento intermediário e o plantio convencional o mais afetado pela comunidade infestante. Entre os adubos verdes plantados em sucessão a mucuna se destacou, sendo seu efeito supressor das plantas infestantes mais importante em áreas cultivadas com manejo de solo convencional.